Morbidity pattern of school children: a study conducted in the urban field practice area of a tertiary health care centre of Odisha, India - Kar, Krishna; Pradhan, Sasmita; Samal, Barada P. (International Journal of Research in Medical Sciences, 2018)
Background: School is acknowledged as the place where children gain knowledge from health education sessions on various aspects of personal hygiene, sanitation and social customs. Health is one of the key factors determining the enrollment, performance and continuation in school. Objective was to study the morbidity pattern of school children. Methods: The present cross sectional study was conducted in selected schools (both govt. and Private) of urban field practice area of SCB Medical College, Cuttack, Odisha during January 2016 to December 2016. A total of 660 school going children were taken for the study. After taking informed consent of the head of the school data was collected by using a Pre-designed, pre-tested questionnaire. Clinical examination was conducted to detect any morbidity pattern. Results: In the present study most common morbidity detected was pallor (47.6%) followed by skin disease (34.5%) and dental caries (23.2%). Other morbidities found were acute respiratory infections 21.9%, eye problems 21.4%, fever 6.8%, pain abdomen 3%, diarrhoea 3.2%, ear discharge 3.9%, headache 5% and rhinitis 3.9%. Conclusions: More emphasis should be given on primordial and primary preventive measures for prevention of childhood morbidities. School based health education programme may be a useful effort in this regard.